Analisis Anggaran Bahan Baku sebagai Alat Pengendalian Biaya Produksi pada Perusahaan Manufaktur - Naurah Ramadhani Siregar; Leoni Geraldin Br Simamora; Jese Marvel Lumban Tobing (Perkumpulan Konsultan Manajemen Pendidikan Indonesia (PKMPI), 2026)
This research aims to analyze the role of the raw material budget as a means of controlling production costs in manufacturing companies by using the literature study method. The research results show that the raw material budget serves as a planning and control tool that helps companies in managing the needs and use of raw materials efficiently. Comparison between budget and realization allows companies to identify deviations that are influenced by internal and external factors. Good budget implementation, including the use of flexible budgets and appropriate control systems, can increase efficiency and reduce waste. However, the effectiveness still depends on the accuracy of its preparation and implementation.